Germline mutations in the VHL gene associated with 3 different renal lesions in a Chinese von Hippel-Lindau disease family - Yuan, Ping (Cancer Biol Ther, 2016)
Von Hippel–Lindau (VHL) disease is a rare autosomal dominant inherited cancer syndrome that is characterized by hemangioblastomas in the central nervous system and retina, renal cell carcinoma and cysts, pancreatic tumors and cysts, and pheochromocytoma. The underlying gene in this disease is the VHL tumor suppressor gene. We characterized a family with 2 affected siblings. The brother and sister displayed VHL type 2B and type 2A features, respectively. Renal lesions in the brother exhibited 3 different phenotypes, including simple renal cysts, multilocular cystic renal cell carcinoma and clear cell renal cell carcinoma. The phenotypes of the 3 concurrent renal lesions were first reported in this study. Mutation detection of the VHL gene revealed 2 recurrent mutations, namely c.256C>T (p.P86S) and c.340 + 5G > C. The former was predicted to be deleterious and to destabilize the hydrophobic core and lead to VHL dysfunction; however, the latter was predicted to be a benign variant. Our findings provided new data for the genotype-phenotype of VHL diseases and elucidated the pathogenic mechanism with in silico analysis.